Assessment of the Critical Period Hypothesis among Adult Fulbe Adamawa in the Traditional Way of Learning the Glorious Quran - Garba, Malami Muhammad; Mohamed Adnan, Mohamad Azrien; Zailani, Muhammad Azhar (Jurnal Usuluddin, 2023)
The CPH has been one of the key areas in Applied Linguistics and Second Language Acquisition (SLA). With the inconclusive debate on the matter among scholars and researchers, this paper attempts to investigate it among adult Fulbe Adamawa in the traditional way of learning the Glorious Qur’an. Data were collected using interview and reading test. Results showed that CPH was a reality. But contrary to the opinions of the mainstream researchers, the Qur’an maintains that human being denigrates mentally and physically as he grows with no specification to puberty period. Wrong methodology and CPH were identified as the barrier to nativism in learning the Qur’an among adult Fulbe Adamawa. Using L1 (Fulfulde) in teaching the Qur’an is not the best method. The study recommends the use of the best methodology which is teaching the Qur’an in the Arabic language and Arabic alphabets.